2017
DOI: 10.1111/andr.12374
|View full text |Cite
|
Sign up to set email alerts
|

miR‐2909 regulates ISGylation system via STAT1 signalling through negative regulation of SOCS3 in prostate cancer

Abstract: One of the well-document strategies adopted by tumour cells for progression is to evade immune surveillance mechanisms. An understanding of the tight interaction between immunity and progression of cancer can provide novel treatment options for different malignancies including prostate cancer (PCa). Here, we have shown that AATF genome encoded miR-2909, known to play role both in immunity and cancer upregulates various interferon stimulating genes (ISGs) including ISGylation system through STAT1. Our results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…Further internalization of miR‐2909 enriched exosomes by the target cells may contribute to the regulation of genes encoding tumour suppressors/oncogenes or involved in immune surveillance within such cells. This view is in conformity with our earlier reported findings regarding the role of cellular miR‐2909 RNomics in the regulation of genes coding for tumour suppressors/oncogenes as well as those that govern immunity . By making use of archetype cellular models (ie, T‐24 and PC‐3 cell lines), the present study revealed that increased post‐transcriptional 3′‐end uridylation of miR‐2909 is the driving force for the recruitment of this miRNA to the exosomes secreted by the prostate cancer cells (PC‐3, Figure C).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Further internalization of miR‐2909 enriched exosomes by the target cells may contribute to the regulation of genes encoding tumour suppressors/oncogenes or involved in immune surveillance within such cells. This view is in conformity with our earlier reported findings regarding the role of cellular miR‐2909 RNomics in the regulation of genes coding for tumour suppressors/oncogenes as well as those that govern immunity . By making use of archetype cellular models (ie, T‐24 and PC‐3 cell lines), the present study revealed that increased post‐transcriptional 3′‐end uridylation of miR‐2909 is the driving force for the recruitment of this miRNA to the exosomes secreted by the prostate cancer cells (PC‐3, Figure C).…”
Section: Discussionsupporting
confidence: 92%
“…Human AATF genome, located on the chromosome 17, has evolved to hold AATF protein coding transcript and regulatory noncoding microRNA (miRNA, miR‐2909) within its fold in a fashion that ensures their mutual cooperative regulation . This interplay between AATF and miR‐2909 is responsible for governing of various cellular processes especially cell cycle progression, checkpoint control, and cellular autophagy/apoptosis . The complexity of this genome does not end here because AATF genome‐encoded miR‐2909 has been shown to govern genes that play crucial role in cancer and immunity, thereby behaving like a double‐edged sword.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another downstream effector of STAT1 is ISG15 , an ubiquitin-like modifier that binds to cytoplasmic and nuclear proteins ISGylating them. ISG15 has not only an anti-viral role, as assumed at the beginning, but also an oncogenic role [36,37]. In our study, both direct STAT1 interaction partners showed nominally increased expression for different mutations.…”
Section: Discussionsupporting
confidence: 63%
“…Further, it was observed that miR-2909 overexpression modulated ISGylation through STAT1 mediated via negative regulation of SOCS3. A significant upregulation of STAT1 phosphorylation and downregulation of SOCS3 was detected in miR-2909-overexpressing PC3 cells whereas miR-2909 plasmid coupled with antagomiR-2909 treatment significantly downregulated phosphorylated STAT1 and upregulated SOCS3 expression [29]. The SOCS3 is a welldocumented inhibitor of JAK/STAT pathway and STAT1 phosphorylation is always reported as inversely correlated with SOCS3 expression [30].…”
Section: Mir-2909 and Isgylationmentioning
confidence: 99%